2015 IEEE International Symposium on Information Theory (ISIT) 2015
DOI: 10.1109/isit.2015.7282691
|View full text |Cite
|
Sign up to set email alerts
|

Fourier analysis of MAC polarization

Abstract: One problem with MAC polar codes that are based on MAC polarization is that they may not achieve the entire capacity region. The reason behind this problem is that MAC polarization sometimes induces a loss in the capacity region. This paper provides a single letter necessary and sufficient condition which characterizes all the MACs that do not lose any part of their capacity region by polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…We have shown that cq-MAC polarization can induce a loss in the symmetric capacity region. A necessary and sufficient condition for J pol (W ) = J (W ) in the case of classical MACs was given in [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that cq-MAC polarization can induce a loss in the symmetric capacity region. A necessary and sufficient condition for J pol (W ) = J (W ) in the case of classical MACs was given in [19].…”
Section: Discussionmentioning
confidence: 99%
“…Generalizing the results of [19] to cq-MACs is an open problem. We note that the condition in [19] was given in terms of the Fourier transform of the probability distribution of one input conditioned on the output and on the other input.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation